Electrochemotherapy enhances the efficacy of Asparagus officinalis, Arum elongatum and Urtica dioica extracts in breast cancer treatment - Yetişsin, Fuat; Alkış, Mehmet Eşref (My University, 2025)
The aim of the current study was to determine the phenolic substances in the stem of Asparagus officinalis L, leaves of Arum elongatum Steven and Urtica dioica L. plants collected from different regions and their cytotoxicities on MCF-7 human breast cancer cell line and to reveal the effects of electroporation (EP) on the antiproliferative activities of these plants. Antiproliferative activities of plant extracts were determined in MCF-7 human breast cancer cells, and their biocompatibility was determined in L-929 fibroblast cells by MTT analysis method. In electrochemotherapy (extract+EP) applications of MCF-7 human breast cancer cells, eight square wave electrical pulse sequences with an intensity of 800 V/cm were used with various doses of plants extracts. It was found that all three plant extracts were rich in phenolic compounds and only A. elongatum showed a relative cytotoxic effect on L-929 fibroblast cells. However, MCF-7 cancer cells showed very good sensitivity to the cytotoxic activities of A. officinalis, A. elongatum and U. dioica extracts, with IC50 values of 443.57, 361.88, and 448.55µg/mL, respectively. It was observed that with EP application, the cytotoxic activity of all three plant extracts on cancer cells increased significantly compared to extract application and cell viability percentages decreased significantly. As a result, our findings suggest that A. officinalis, A. elongatum and U. dioica extracts have anticancer potential and may be promising for breast cancer when used with EP.
Keywords: Breast cancer, Electroporation, Herbal treatment, Phenolic substances